Consequences of Health Insurance Cost Sharing Among Low‐Income Medicare Beneficiaries: Evidence from Benefit Cliffs in Medicaid and Medicare's Prescription Drug Subsidy Program. (20th August 2020) - Roberts, E.; Glynn, A.; Donohue, J.; Michael McWilliams, J.; Gellad, W.; Cornelio, N.; Sabik, L.
Abstract : Research Objective: Cost sharing is intended to mitigate the effects of moral hazard in health insurance but can have unintended consequences if patients underuse medically beneficial care that is subject to out‐of‐pocket costs. The Medicare program requires substantial cost sharing, including deductibles and coinsurance for outpatient care and prescription drugs. However, little is known about the consequences of this benefit design for low‐income Medicare beneficiaries who do not qualify for Medicaid or Part D Low‐Income Subsidies (LIS), which defray these costs. In this study, we harnessed quasi‐random variation in exposure to Medicare cost sharing, resulting from "cliffs" in cost sharing subsidies above vs. below income eligibility thresholds for Medicaid and the LIS, to assess the effects of cost sharing on low‐income beneficiaries' out‐of‐pocket spending and use of care. Study Design: We conducted regression discontinuity analyses using detailed household income data from the Health and Retirement Study (HRS) linked to Medicare claims. Our study design compared Medicare beneficiaries with incomes above vs. below eligibility thresholds for the Qualified Medicare Beneficiary (QMB) program, a Medicaid benefit that eliminates cost sharing in Medicare Parts A and B for beneficiaries <100% of the Federal Poverty Level (FPL), and the LIS, which reduces prescription drug costs for persons <150% of FPL. Beneficiaries whose income just exceeds these thresholds face substantially higher out‐of‐pocket costs in Medicare despite having only modestly higher incomes. Population Studied: Respondents to waves 9‐13 of the HRS (2008‐2016 survey years) enrolled in the fee‐for‐service Medicare program with incomes <250% of the FPL in the survey year. We conducted separate regression discontinuity analyses among individuals with incomes 0‐135% of FPL (spanning the QMB eligibility threshold; N = 5, 121 person‐years) vs. 136‐250% of the FPL (spanning the LIS eligibility threshold; N = 7, 315 person‐years). Principal Findings: We found pronounced discontinuities in QMB and LIS enrollment at these programs' eligibility thresholds: 51 percentage points (pp) at the QMB threshold and 27pp at the LIS threshold. Beneficiaries whose income exceeded the QMB threshold incurred 20% fewer prescription drug claims, had 12% fewer physician office visits, and were 59% more likely to report having high (>$2, 000) out‐of‐pocket medical costs, relative to beneficiaries whose income was below this threshold. Beneficiaries whose income exceeded the LIS threshold had 17% fewer prescription drug claims and were 16% more likely to have high out‐of‐pocket costs. We found no discernable differences in inpatient utilization above vs. below either threshold. Conclusions: Our findings show how cost sharing obligations in the Medicare program affect low‐income beneficiaries' use of care: beneficiaries whose income just exceeds thresholds at which these cost sharing obligations are eliminated or appreciably reduced use substantially fewer prescription drugs and, in some cases, outpatient care. Implications for Policy or Practice: Medicare beneficiaries with minimally different incomes can face substantially different out‐of‐pocket costs that affect their use of care. Extending Medicaid and LIS cost sharing subsidies to additional near‐poor beneficiaries, and gradually tapering assistance for individuals with modestly higher incomes, could alleviate the impacts of Medicare's cost sharing obligations on near poor beneficiaries' use of care. Primary Funding Source: Agency for Healthcare Research and Quality.